Cracks, microcracks and fracture in polymer structures: Formation, detection, autonomic repair. (October 2016) - Awaja, Firas; Zhang, Shengnan; Tripathi, Manoj; Nikiforov, Anton; Pugno, Nicola
Abstract: Polymers and polymer composites are susceptible to premature failure due to the formation of cracks and microcracks during their service time. Evolution of cracks and microcracks could induce catastrophic material failure. Therefore, the detection/diagnostics and effective repair of cracks and microcracks are vital for ensuring the performance reliability, cost effectiveness and safety for polymer structures. Cracks and microcracks, however, are difficult to detect and often repair processes are complex. Biologically inspired self-healing polymer systems with inherent ability to repair damage have the potential to autonomically repair cracks and microcracks. This article is a review on the latest developments on the topics of cracks and microcracks initiation and propagation in polymer structures and it discusses the current techniques for detection and observation. Furthermore, cracks and microcrack repair through bio-mimetic self-healing techniques is discussed along with surface active protection. A separate section is dedicated to fracture analysis and discusses in details fracture mechanics and formation.